(3QSGdg aj HjGf ebOeGJ SHY jMJGL aj eYQag bhS bRM Gdj eYQaJgGs - (3eLghds
(3ChdgG (B:s
(3HSe Gddg gPg QSGdI aj HjGf ebOeGJ SHY jMJGL aj eYQaI bhS bRM Edi eYQaJgG GdebOeI GdChdi efgG aj HjGf GdGfYcGS hgj Cfg EPG hbY GdVhA ef LSe eVjA Ydi LSe eUbd GfYcS Pdc GdVhA s
(3BNQgG (B:s
(3GdebOeI GdSGHYI EPG cGfJ GdfSHI Hjf GdQGFj hHjf CLRGA GdeQBI aj GdhVY fSHI Hjf hGMOI hcPdc GdfSHI Hjf cd hGMO CLRGA GdeQBI hHjf GdeQFj aj GdhVY hGMOI Jes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs